The Historical Role of the European Shadow Banking System in the Development and Evolution of Our Monetary Institutions - Israel Cedillo Lazcano (City, University of London, City Political Economy Research Centre (CITYPERC), 2013)
When we hear about the 2008 Lehman Brothers crisis, immediately we relate it to the concept of "shadow banking system"; however, the credit intermediation involving lightly regulated entities and activities outside the traditional banking system are not new for the European Financial Systems, after all, many innovations developed in the past, were adopted by European nations and exported to the rest of the world (i.e. coinage and central banking), and European innovators unleashed several financial crises related to "shadowy" financial intermediaries (i.e. the Gebroeders de Neufville crisis of 1763). However, despite not many academics, legislators and regulators even agree on what "shadow banking" is, this latter does not refer exclusively to the functions of credit intermediation and maturity transformation. This concept also refers to the creation of assets such as digital media of exchange which are designed under the influence of Friedrich Hayek and the Austrian School of Economics. This lack of a uniform definition of "shadow banking" has limited our regulatory efforts on key issues like the private money creation, a source of vulnerability in the financial system that, paradoxically, at the same time could result in an opportunity to renovate European institutions, heirs of the tradition of the Wisselbank and the Bank of England which, during the seventeenth century, faced monetary innovations and led the European monetary revolution that originated the current monetary and regulatory practices implemented around the world.
Keywords: 330; Europe; shadow banking; world-system; central banking; financial innovation; regulation